Opportunities and Challenges in Implementing CRM in Class C Private Hospitals: A Case Study - Jeffry Rustandi; Benny Ranti; K P Suharyono; Marisi Pakpahan (International Forum of Researchers and Lecturers, 2024)
This study examines the opportunities and challenges of implementing Customer Relationship Management (CRM) in Class C private hospitals in Bogor, Indonesia. Using a mixed-methods approach, the research combines qualitative and quantitative analyses, including SWOT and Quantitative Strategic Planning Matrix (QSPM) methods, to identify the most effective CRM model. Findings reveal the hospital's internal strengths, weaknesses, external opportunities, and threats, offering strategies to improve patient engagement and operational efficiency. The results emphasize the critical role of digital transformation, staff training, and strategic adaptation to meet the needs of non-BPJS patients in a rapidly evolving healthcare landscape. The research contributes significantly to the development of CRM models tailored to healthcare institutions in emerging market..